Conditional payments for democracy to local leaders managing natural resources in rural Namibia - Ivo Steimanis; Esther Blanco; Björn Vollan (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2024)
In this study, we provide causal evidence on the capacity of monetary incentives to encourage real-life local leaders managing water and land to improve their procedural fairness. We report results from incentivized decisions and surveys conducted with local leaders in rural Namibia (n=64) and their constituents (n=384). Conditional payments are introduced in a setting where leaders can select among different rules that vary in their perceived procedural fairness in distributing a monetary allocation. In a within-subject design we randomly introduce a small or large conditional payment for allowing for a vote. The majority of leaders (64%) embrace democratic decision-making initially. With paymentsthere is a significant reduction in autocratic leadership, by switching mainly to appearing democratic while keeping control, but with no significant increase in truly democratic leadership. Explorative analyses reveal that the effects are mainly driven by extrinsically motivated leaders to govern, who are less democratic initially and who reap the conditional payments without effectively including constituents in the decision process. Our findings suggest that simply introducing conditional payments for democratic choices may not be sufficient to promote democratization of local governance for the management of natural resources, and caution against their blueprint use in pluralistic governance settings.
Keywords: D7; Q2; Q5; C9; 330; local governance of common pool resources; social norms; conditional payments; economic experiment